(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The hip bone is a big, flattened, asymmetrical bone that is narrowed in the middle and enlarged above and below. Together, they form the sides and anterior wall of the pelvic cavity. It meets its counterpart on the opposing side in the middle line in front. Aim: Morphometric study of the acetabulum of dry hip bone in relation to sexual dimorphism in north Indian population. Method: The study is cross sectional. Material for the study consisted of 300 dry hip bones of known gender. Gender was determined using information from the Department of Anatomy Index Medical College Malwanchal University Indore M.P. All the bones are fully ossified and free from any congenital or pathological defects. Deformed and malformed bones are also excluded from the study. Not properly ossified and not paired bones were excluded. Results and Conclusion: The vertical, transvers, anterior, posterior diameter and depth of acetabulum were found significant difference between male and female.